Comunidade de macrófitas aquáticas em uma lagoa temporária no semiárido brasileiro: variações estruturais e coexistência de espécies - Tabosa, Alyne Bezerra (2010)
Identify whether communities are structured randomly or based on bio logical interactions is one of the most important aspect in ecology. In this sense the identification of events involved in the succession of species can significantly contribute. The temporary ponds in the semi-arid environments are temporary wet, with distinctive features that allow a rapid species succession, as they present environmental variations, wet and dry phase, responsible for the selection of species according to their ways of life. These environments present communities, which emphasize the aquatic macrophytes, adapted to seasonal flooding periods. So, it came up to describe the variations in the structure of a aquatic macrophytes community in a temporary pond, during the flooding period, relating the changes in dominance and species composition to environmental variables. As well, raising considerations of co-occurrence of species through the c-score. Data samples were made fortnightly by the method of points in order to obtain data on the stratification, composition of dominant species in the community, totaling 13 samples. In addition to the vegetation data were also obtained data for pH, conductivity, turbidity, alkalinity, total nitrogen, nitrate, total phosphate, orthophosphate, dissolved oxygen and biochemical oxygen demand of water. These were related to the data of dominance of species showing that environmental variables affect different forms of the species studied. The c-score was both calculated for each sample individually and for the duration of flooding. For the each sample separate ly prevailed biological interactions in the community and considering the whole period the c-score shows an occupation of the species according to a pattern of succession.